2009
DOI: 10.1111/j.1365-2036.2009.03964.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: effects of botulinum toxin on levator ani syndrome – a double‐blind, placebo‐controlled study

Abstract: SUMMARY BackgroundLevator ani syndrome is characterized by anorectal discomfort ⁄ pain, treatment of which is unsatisfactory. We hypothesized that Botulinum toxin relieves spasm and improves symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 23 publications
(30 reference statements)
0
24
0
1
Order By: Relevance
“…Most studies that include Botox treatment for LS consist of very few patients and the dose of Botox injected has ranged between 20 and 100 units. One study showed that a dose of 100 units of Botox did not show any differences in physiological test results and pain scores between the placebo and Botox groups [19]. Another study showed symptom improvement after 80 units of Botox when compared to placebo [20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most studies that include Botox treatment for LS consist of very few patients and the dose of Botox injected has ranged between 20 and 100 units. One study showed that a dose of 100 units of Botox did not show any differences in physiological test results and pain scores between the placebo and Botox groups [19]. Another study showed symptom improvement after 80 units of Botox when compared to placebo [20].…”
Section: Discussionmentioning
confidence: 96%
“…Invasive options include bilateral injection therapy with a triamcinolone and Lidocaine mixture at trigger points in the levator muscle and Botox injections. All of these options have been described in the literature as having varied success rates [2,6,19,20,21]. Most studies that include Botox treatment for LS consist of very few patients and the dose of Botox injected has ranged between 20 and 100 units.…”
Section: Discussionmentioning
confidence: 97%
“…Abbott et al [38] performed a randomized controlled trial of BTX injected transvaginally into the puborectalis and pubococcygeus for levator/pelvic floor spasms in women, and demonstrated a decrease in manometry pressures and an improvement in dyspareunia. In contrast, in a more recent study of a cohort of men and women, following peri-anal BTX-A injection for levator ani syndrome showed decreased anal manometry pressures but without significant changes in pain score [39]. The authors felt that the failure of the BTX to improve symptoms could be due too pain originating in the puborectalis and not the injected anal sphincter, or that pathophysiology of the pain does not involve spasms.…”
Section: Btx-a In the Treatment Of Cpps: Somatic Nerve Targetsmentioning
confidence: 85%
“…Finally, a recent double-blind, placebo-controlled study showed that intrasphincteric injection of 25 IU of botulinum toxin A (Allergan, Irvine, California, USA) did not change the frequency, intensity or pain episodes when compared to placebo, suggesting that botox may be ineffective. 60 …”
Section: A2 Unspecified Functional Anorectal Painmentioning
confidence: 97%